Gut dysbiosis induced by a high-salt diet aggravates atherosclerosis by increasing the absorption of saturated fatty acids in ApoE-deficient mice - Ushigome, Emi; Yoshimura, Takashi; Yuge, Hiroki; Ogata, Takehiro; Okamura, Takuro; Hamaguchi, Masahide; Fukui, Michiaki; Hosomi, Yukako; Kimura, Tomonori; Nakanishi, Naoko; Sasano, Ryoichi (Journal of Clinical Biochemistry and Nutrition, 2025)
Excessive salt intake has been associated with gut dysbiosis and increased cardiovascular risk. This study investigates the role of gut dysbiosis induced by a high-salt diet in the progression of atherosclerosis in ApoE-deficient mice. Sixteen-week-old male ApoE-deficient mice were fed either a high-fat, high-sucrose diet or high-fat, high-sucrose diet supplemented with 4% NaCl for eight weeks. The group on the HFHSD with high salt showed significant progression of atherosclerosis compared to the high-fat, high-sucrose diet group. Analysis of the gut microbiota revealed reduced abundance of beneficial bacteria such as Allobaculum spp., Lachnospiraceae, and Alphaproteobacteria in the high-salt group. Additionally, this group exhibited increased expression of the Cd36 gene, a transporter of long-chain fatty acids, in the small intestine. Serum and aortic levels of saturated fatty acids, known contributors to atherosclerosis, were markedly elevated in the high-salt group. These findings suggest that a ‍high-salt diet exacerbates atherosclerosis by altering gut microbiota and increasing the absorption of saturated fatty acids through upregulation of intestinal fatty acid transporters. This study provides new insights into how dietary salt can influence cardiovascular health through its effects on the gut microbiome and lipid metabolism.